Adaptations to the current ECCO/ESPGHAN guidelines on the management of paediatric acute severe colitis in the context of the COVID-19 pandemic: a RAND appropriateness panel. Issue 6 (1st September 2020) - Hansen, Richard; Meade, Susanna; Beattie, R Mark; Auth, Marcus KH; Croft, Nick; Davies, Philip; Devadason, David; Doherty, Conor; Epstein, Jenny; Howarth, Lucy; Kiparissi, Fevronia; Muhammed, Rafeeq; et al.
Abstract : Objective: Paediatric acute severe colitis (ASC) management during the novel SARS-CoV-2/COVID-19 pandemic is challenging due to reliance on immunosuppression and the potential for surgery. We aimed to provide COVID-19-specific guidance using the European Crohn's and Colitis Organisation/European Society for Paediatric Gastroenterology, Hepatology and Nutrition guidelines for comparison. Design: We convened a RAND appropriateness panel comprising 14 paediatric gastroenterologists and paediatric experts in surgery, rheumatology, respiratory and infectious diseases. Panellists rated the appropriateness of interventions for ASC in the context of the COVID-19 pandemic. Results were discussed at a moderated meeting prior to a second survey. Results: Panellists recommended patients with ASC have a SARS-CoV-2 swab and expedited biological screening on admission and should be isolated. A positive swab should trigger discussion with a COVID-19 specialist. Sigmoidoscopy was recommended prior to escalation to second-line therapy or colectomy. Methylprednisolone was considered appropriate first-line management in all, including those with symptomatic COVID-19. Thromboprophylaxis was also recommended in all. In patients requiring second-line therapy, infliximab was considered appropriate irrespective of SARS-CoV-2 status. Delaying colectomy due to SARS-CoV-2 infection was considered inappropriate. Corticosteroid tapering over 8–10 weeks was deemed appropriate for all. After successful corticosteroid rescue, thiopurine maintenance was rated appropriate in patients with negative SARS-CoV-2 swab and asymptomatic patients with positive swab but uncertain in symptomatic COVID-19. Conclusion: Our COVID-19-specific adaptations to paediatric ASC guidelines using a RAND panel generally support existing recommendations, particularly the use of corticosteroids and escalation to infliximab, irrespective of SARS-CoV-2 status. Consideration of routine prophylactic anticoagulation was recommended.